How daily code mixing becomes a new strategy for teaching vocabulary mastery - Muh Mahrup Zainuddin Sabri; Bambang Widi Pratolo; Pegiawan Basopi (Intelektual Pustaka Media Utama, 2019)
Vocabulary learning is an integral part of foreign language learning. The meaning of new words is very often emphasised, both in books and in verbal communication. Vocabulary is considered a centre of language teaching and is very important for language learners. This study found a daily code-mixing strategy in learning English vocabulary in the second grade of secondary school. The method used is qualitative and quantitative. The research phase includes pre-test and post-test, questionnaire and interview. The findings show that there is an influence on the level of student skills in using the strategy. Furthermore, it also found that students with higher vocabulary levels tended to take lessons in class interactively, this became fun, and students could motivate themselves they usually succeeded in learning by asking, monitoring and evaluating their learning habits. The findings also show that students with low vocabulary levels tend to choose to ignore direction and lack of participation, which means that they do not care about the course of the teacher and still carry unfavourable habits in the classroom. The findings of this study contribute to the further development of existing code-mixing theory and about vocabulary students and strategies. This study refers to giving benefits to classroom practice in the Indonesian context, specifically in increasing EFL teacher awareness so as not to focus solely on existing strategies, but rather look at the phenomena that occur around to create new strategies in teaching English.